Formative Evaluation for the fifth Year Medical Student in Clinical Radiology by Pre-test and Post test - Aphinives, Chalida; Mairiang, Eimorn; Srinakarin, Jiraporn; Chaiyakum, Jitjaroen; Hanpanich, Petcharakorn; Thammaroj, Jureerat; Nitinavakarn, Benjaporn (Srinagarind Medical Journal, 2013)
Background: Evaluation is one of the essential parts of education. Before the academic year 2003, only final examination was used to evaluate students’ knowledge in Department of Radiology, Faculty of Medicine, Khon Kaen University. Objective: To compare students’ knowledge in diagnostic radiology between pre- and post-learning periods. Subject and Method: All the fifth-year medical students in the academic year 2003 were divided into 12 groups (10-15 per group), total 156 students. Each group rotated to attend in diagnostic radiology for 2 weeks. Each student was evaluated by pre- and post-tests which were the same test. Result: One hundred and fifty-two students (97.43%) showed improvement in their knowledge. The average score of the pre-test was 6.8, while that of the post-test was 10.91. There was no relationship between the score and final grade, except 4 students who got same score from the tests. They also got low score from the final examination, both theory and practice sections. Conclusion: Students had more knowledge in diagnostic radiology after learning.